متطلبات الافصاح الالكتروني للقوائم المالية في الجزائر - بلول, محمد الصالح; قويدر, محمد الطيب; رفيق, الازهر (University of eloued جامعة الوادي, 2017)
The objective of our study is to identify electronic disclosure, and define a framework for the electronic disclosure requirements of financial statements in Algeria.Where electronic disclosure has become a widespread concern of companies in developed countries, to cope with the rapid technological developments, and to meet the users of the financial statements. Moreover, to obtain timely and good information. In order to achieve the objectives of the study, we relied on the theoretical aspect related to the subject in several aspects related to accounting disclosure on the one hand, and electronic disclosure on the other hand, as well as the formulation of some hypotheses. By use a questionnaire to reach answers to the problem that is posed.
مذكرة ماستر تدقيق محاسبي
Keywords: الافصاح، الافصاح الالكتروني، القوائم المالية; Disclosure, Electronic Disclosure, Financial Statements.